Sales and Inventory Applications on Davinci Acoustic Medan Based on Mobile Application - Rio Rio Raynaldi L Tobing; R. I. E. Saragih; Eviyanti Purba (Geviva Publisher, 2022)
The development of information technology at this time, bringing updates to everyone both in the means of communication and to buying and selling methods that are not left behind by their impact, the rapid development of information technology makes it easier for people to sell and buy goods online, both via the web and on mobile devices. now often referred to as Android. Android makes it very easy for people to sell and buy goods, because Android uses information technology, namely web and mobile-based applications that are connected to the internet network, so people no longer need to come to the store first to sell and buy goods. In this final project, it will discuss the design of a mobile application-based Davinci Acoustic Medan store sales and inventory application by facilitating customer registration, ordering information, payment confirmation and stock checking.